Synthesis and characterization of magnetite nanoparticle for removal of heavy metal ions from aqueous solutions. Issue 1 (1st April 2022) - Sampora, Yulianti; Hardiansyah, Andri; Hikmat; Khaerudini, Deni Shidqi; Burhani, Dian; Sondari, Dewi; Septiyanti, Melati; Septevani, Athanasia Amanda
Abstract: Synthesis and characterization of magnetite-nanoparticles (MNc) were successfully carried out by coprecipitation of both Fe 3+ and Fe 2+ ions for the potential use in the environmental application. The obtained MNc was characterized by VSM (Vibrating Sample Magnetometer), X-Ray Diffraction, and Scanning Electron Microscopy, and then it was compared to the commercially available magnetite (MNo). Inductively Coupled Plasma-Optical Emission Spectrometry (ICP-OES) is also carried out to investigate the adsorption efficiency of the obtained MNc towards various types of heavy metals. The resulting MNc was superparamagnetic, as noted by a zero coercivity value. The pure MNc synthesized in this study showed X-Ray Diffraction patterns of several peaks in the 2θ range of 5° to 70°, which were the main characteristic peaks of the crystal plane indicating the formation of magnetite nanoparticles. These results show a higher purity of magnetite than that of MNo. Based on the Scherrer method, the main crystal size of magnetite nanoparticles was around 9.859958 nm. Further, the SEM results showed that the morphology of Fe3 O4 was spherical nanoparticles, but they tended to agglomerate into large particles with a size of about 1.5 ± 0.9 μm. The ICP analysis showed that the obtained MNc could adsorb several types of heavy metal ions, such as Cd, As, Cr, Se, Ti, Ni, Pb, Be with a percentage of efficiency in the range of 3-64%. As expected, the MNc also afforded better metal ions adsorption performances compared to commercially available magnetite (MNo).